Design of Motor Control Center Panel for Controlling of Two Three Phase Induction Motors Based on PLC and VSD - Adam, Muhamad Feisal; Zukhrufi, Andhika Nadhif; Yafi Syuhada, Muhammad Ghaly; Kusnadi, Kusnadi; Halimi, Imam (SAINTEKBU, 2023)
A Motor Control Center (MCC) Panel is a control panel that functions as the control centre of two or more induction motors in buildings and the industrial world. However, the induction motor control panel in PNJ electrical engineering is still controlled to control one VSD, not yet to control two VSDs for two three-phase induction motors. Therefore, we need an MCC panel that implements modern industrial control using PLC and VSD so that it can be used for the practical application of three-phase induction motor control in the industrial world for PNJ electrical engineering students. The method used is literature study, MCC panel design with VSD and PLC, data retrieval, and data analysis. The results obtained from this study are that two VSDs were successfully controlled from a PLC using the Modbus RTU RS-485 communication protocol. There are differences in the actual measurement results of voltage and current using measuring instruments with VSD readings up to 91.1% for voltage and 48.68% for current caused by two factors, namely human error and measuring instrument error.